Legislasi dalam Pemerintahan Islam: Antara Otoritas Wahyu dan Dinamika Sosial - Aulia, Astri; Aziza, Nurul; Kurniati (Cendekia Inovatif Dan Berbudaya, 2025)
This study is motivated by the complexity of the legislative system in Islamic governance, which integrates divine revelation with the dynamic needs of society. Unlike secular legal systems that rely solely on human rationality, Islamic legislation is rooted in the Qur'an and Sunnah, and further developed through ijtihad methods such as ijma', qiyas, and maqashid al-shari'ah. The objective of this research is to examine the fundamental principles of legislation in Islam, its relationship with public policy, and the challenges of its implementation in contemporary Muslim-majority states. The research applies a normative juridical method, supported by conceptual and sociological approaches, with qualitative descriptive analysis. The findings reveal that the Islamic legislative system is flexible and responsive to social change while maintaining its normative integrity through instruments such as maqashid al-shari’ah and siyasah syar’iyyah. Islamic legislation demonstrates the capacity to adapt to modern governance frameworks, as long as it remains grounded in the values of justice, public interest, and human rights protection.